ИСТОРИЈАТА НА ЖИВОТОТ ВО ЌОРСОКАК: ПОМЕЃУ ПРИКАЗНАТА И ИЛУЗИЈАТА (Philological Studies, 2019)
The aim of this paper is to represent the challenging interrelationship between traditional and modern folk narrative researches, in order to show the position of life history as a folklore genre. The discussion of this topic leads to the most general and profound issues of the theory of folklore and anthropology (Asadwskij, Röhrich, Niedermüller, L. Dégh, O. Sirovátka, Stahl, Bausinger and Bourdieu). Some of these researchers concentrate on the concept of individual and identity, in order to show the considerable function of this new folklore genre (Dégh, Sirovatka, Niedermüller); on the other side are researchers that stress the concept of biographical illusion (Bourdieu, Bausinger). Thus, whole 20th century debate could give us one interesting position of this new folklore genre revealing two mentioned concepts: life history as story and illusion.